Measuring the observer (Hawthorne) effect on adenoma detection rates - Taghiakbari, Mahsa; Coman, Diana Elena; Takla, Mark; Barkun, Alan; Bouin, Mickael; Bouchard, Simon; Deslandres, Eric; Sidani, Sacha; von Renteln, Daniel (Endoscopy International Open, 2023)
Background and study aims An independent observer can improve procedural quality. We evaluated the impact of the observer (Hawthorne effect) on important quality metrics during colonoscopies.Patients and Methods In a single-center comparative study, consecutive patients undergoing routine screening or diagnostic colonoscopy were prospectively enrolled. In the index group, all procedural steps and quality metrics were observed and documented, and the procedure was video recorded by an independent research assistant. In the reference group, colonoscopies were performed without independent observation. Colonoscopy quality metrics such as polyp, adenoma, serrated lesions, and advanced adenoma detection rates (PDR, ADR, SLDR, AADR) were compared. The probabilities of increased quality metrics were evaluated through regression analyses weighted by the inversed probability of observation during the procedure.Results We included 327 index individuals and 360 referents in the final analyses. The index group had significantly higher PDRs (62.4% vs. 53.1%, P=0.02) and ADRs (39.4% vs. 28.3%, P=0.002) compared with the reference group. The SLDR and AADR were not significantly increased. After adjusting for potential confounders, the ADR and SLDR were 50% (relative risk [RR] 1.51; 95%, CI 1.05–2.17) and more than twofold (RR 2.17; 95%, CI 1.05–4.47) more likely to be higher in the index group than in the reference group.Conclusions The presence of an independent observer documenting colonoscopy quality metrics and video recording the colonoscopy resulted in a significant increase in ADR and other quality metrics. The Hawthorne effect should be considered an alternative strategy to advanced devices to improve colonoscopy quality in practice.
Keywords: Polyps / adenomas / ...; Endoscopy Lower GI Tract; Colorectal cancer; CRC screening; Endoscopic resection (polypectomy, ESD, EMRc, ...)